Strategic planning for a micro enterprise: case study in a supermarket in Rio Grande do Sul (Research, Society and Development, 2020)
This study aimed to develop a strategic planning for a microenterprise of the food products trade of the state of Rio Grande do Sul. The research was classified as the approach, as deductive, quantitative and qualitative; Regarding the procedures, the research is descriptive, exploratory and a case study; and used interview technique for data collection and Microsoft Excel® spreadsheet for data analysis. During the study the five stages of strategic planning were carried out, which include defining the business, mission, vision and principles, evaluating the internal and external environments, building the strategic posture, elaborating the strategic objectives and goals, and creating action plans to monitoring. The study concludes that Alpha Supermarket is in the strategic development posture, where it is possible to potentialize strengths and maximize opportunities.